Feminisme Vis A Vis Patriarki Dalam Islam - Wahyu Trisno Aji (UIN Mataram, 2022)
The existence of women is treated differently from the existence of the opposite sex, namely men. This differentiation occurs since time immemorial where humans have recognized themselves as the most conscious species. Humans called women themselves are treated like objects. Women must be subordinate to men, and men must dominate women. However, over time, this view has become worthy of a revolution. The view that considers women as second humans must be removed. Women are also human and demand the same rights as men as human beings too. In this article, it will be explained how women should be equal to the roles of men. Feminism is a form of how women fight for themselves to face the rise of patriarchal ideology. Women are also human beings who can also become leaders; this is a revolutionary view of feminism to fight the ideology that subordinates women.